What has luck got to do with economic development? An interpretation of resurgent Asia's growth experience - LEUNG, Hing-Man (Institutional Knowledge at Singapore Management University, 2003)
This paper critically reexamines the belief, currently gathering strength in the literature, that economic development depends on good luck rather than on good policy, and that Prometheus is “unchained by chance”. While it is impossible to disprove the role of luck in growth, we argue that luck is endogenous, and good luck is a function of good policy. Luck favours those who strive. Again contrary to common belief, we show that resurgent Asian economies have endured more, not less, than their fair share of economic volatility. They learned their lessons by success and failures, and luck is endogenous through learning-by-investing.